Validity and reproducibility of VO2max testing in a respiration chamber - Kleinloog, J. P. D.; van Laar, S. P. G. A.; Schoffelen, P. F. M.; Plasqui, G. (Scandinavian Journal of Medicine & Science in Sports, 2021)
The aim of this study was to investigate whether VO2max can be accurately measured in a respiration chamber. Thirty participants aged 23.4 ± 3.9 years with a wide range in VO2max were included. Participants performed four incremental cycle ergometer tests (VO2max) with a minimum of 5 days between tests. These tests consisted of one familiarization test with face mask, followed by two VO2max tests in the respiration chamber and one test with face mask in randomized order. Oxygen consumption and CO2 production were measured continuously using Omnical (Maastricht University, the Netherlands) gas analysis system. The mean VO2max was 3634 ± 766 ml, which resulted in mean VO2max per lean body mass of 60.8 ± 8.0 ml/kg. Repeated respiration chamber tests showed a high concordance, and no significant differences were detected between tests (Lin's concordance correlation coefficient (Rc) = 0.99; ?70 ± 302 ml/min; p = .38). There was high concordance between the mean VO2max from both respiration chamber tests and the mean face mask tests, and no significant difference (Rc = 0.99; Delta41 ± 173 ml/min; p = .22) was observed. The Bland-Altman plots showed no proportional bias between different tests. In conclusion, the respiration chamber has been found to be a valid and reproducible method for measuring VO2max. New research opportunities are possible in the respiration chamber, such as maximal exercise testing during 24-hour measurements.